Interactions Between Chinese Tax Incentives and WTO's Subsidy Rules Against the Background of EU State Aid - Xu, Diheng (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
The book provides insights to the alleviation of tensions between Chinese tax incentives and the WTO's subsidy rules, thus further offering implications for both China and the WTO on integrating in the world economy. Moreover, doing a comparative study with EU State aid law can also provide China with a source of inspiration for reviewing its legal mechanism in respect of tax incentives and the WTO for rethinking its subsidy rules with regard to achieving its objectives and purposes. Academics and students in related subject will be interested to read the book. Practitioners doing business related to China, EU and international trade can be very interested in this book. Policymakers in both China and EU can also get valuable knowledge and inspiration from the book.
Introduction -- Overview of tax incentives as subsidies in the context of international trade and competition: rationale for granting and regulating tax incentives -- Subsidy rules of the WTO and State aid law in the EU -- The internal benchmark and Chinese tax incentives -- Testing Chinese tax incentives against the ASCM and EU State aid law -- The origins of the differences in the testing results -- Recommendations for Chinese tax incentives and the future for the WTO's subsidy rules -- Summary and conclusions.
Keywords: Private international law; Conflict of laws; International law; Comparative law; Mediation; Dispute resolution (Law).; Arbitration (Administrative law).; Trade regulation; Private International Law, International and Foreign Law, Comparative Law; Dispute Resolution, Mediation, Arbitration; International Economic Law, Trade Law